Artistic norms and political standards - issues in the writing of a Philippine literary history - Tolentino, Delfin, L., Jr. (2003)
The study of Philippine literature has advanced considerably since 1967, when literary criticism in the country was said to have come of age with the publication of Brown Heritage: Essays on Philippine Cultural Tradition and Literature. Numerous volumes of textual exegeses and critical assessment have appeared, attesting to the vitality of contemporary literary theory and criticism in Philippine literature as a process or form of development and not merely as an aggrupation of discrete and unrelated texts. Philippine literary history comes in various guises, e.g., accounts of the development of specific genres; investigations on sources and influences, or attribution and authenticity; studies of movements and traditions; and general literary histories. What are the underlying assumptions and principles of these histories? How do they interpret literary development? Is Philippine literary history simply a component of our social and political history, or is it the history of Philippine literature as art? These are the issues discussed in this paper. Through an analysis of major or representative works (e.g., Bienvenido and Cynthia Lumbera's Philippine Literature: A History and Ilnthology; Virgilio S. Almario's Balagrasismo versus Modernismo; Resil Mojares's The Origins and Rise of the Filipino Novel), I hope to define a tension in contemporary constructions of our literary history, as artistic norms and political standards split up or coalesce in the efforts of Filipino scholars to present our literature as a series of related narratives.
Includes bibliographical references (pages 79-81).